The Mediating Effect of Skills Application on the Relationship between Learning and Continuous Improvement - Kristina Sisyuk (International School for Social and Business Studies, 2019)
Perceived urgency for the upskilling of employees is rapidly increasing within political, social, and economic institutions. This brings the danger that companies invest in training and development of employees without understanding its effects in order to enjoy sustainable learning in the workplace. This study explored the mediating role of skills application in the relationship between learning and continuous improvement in a knowledge-intensive company. An employee survey from 2015 of a knowledge-intensive company with a sample of 3,730 employees was utilized to perform mediation analysis with structural equation modelling through the bootstrapping method. The analysis confirmed that learning affects continuous improvement by affecting skills application. The investigated effects are statistically significant and positive. The results provide empirical support on the mediating role and the importance of skills application to see the benefits of learning measures in the workplace. This research is relevant for knowledge-intensive organizations as a way to understand that learning activities in the workplace alone are not sufficient to influence continuous improvement of processes, products, and better ways of working.